A rapid assessment tool for integrated watershed management: a case study from La Plata river in South America - Musálem Castillejos, Karim (2013)
Environment quality indicators can be inadequate when measuring the short-term impacts of projects and actions within an integrated watershed management approach. Quantifiable changes in environmental indicators often take long periods of time –often at the decade level- and are costly in terms of data collection. The subsequent analysis and interpretation seldom reflect the outcomes of work carried out at organizational, inter-institutional and social levels in the short-term. To address this constraint, an Integrated Watershed Management (IWM) assessment methodology based on data collected through key-informants was trialed in sub basins of the La Plata River in South America, and compared to a similar case study carried out in Central America. We applied the assessment tool to the mboi cae/quiteria watershed in Paraguay, and determined progress towards IWM to be 35 % (seen as a global average). We also conducted a detailed evaluation of environmental quality indicators. Comparison with the Central American case study from 2005 allowed a discussion of the methodology and its suitability in different Latin-American contexts. We propose the use of this assessment methodology, based on key-informants and data triangulation, whenever possible to obtain understanding on how projects within an IWM approach can be evaluated in a standardized manner; in a short time; and with low costs. Not substituting, our proposed rapid assessment is not a replacement for ‘proper’ complementary environmental assessment, but offers a rapid and preliminary appraisal of how projects or processes progress with an IWM approach, especially in rural areas.